Major and Trace Element Compositions of Clinopyroxene Phenocrysts in Altered Basaltic Rocks from Yuksekova Complex within Bitlis Suture Zone (Elazig, Eastern Turkey): Implications for the Tholeiitic to Calc-Alkaline Magmatism - Ural, Melek (Mdpi, 2023)
This paper presents major and trace element compositions of the clinopyroxene phenocrysts from variably altered basaltic rocks from the Yuksekova Complex from E Anatolia (Elazig) to reveal the geochemical affinity of the basaltic magmatism and the intensive parameters during magmatic crystallization. The Yuksekova Complex crops out over extensive areas to the north of the Bitlis suture. The investigated samples come from an area of ca. 2500 km(2) in the Elazig province. Petrographically, the basaltic rocks are represented by basalt, porphyric basalt and dolerite. The rocks are characterized by plagioclase, clinopyroxene, magnetite and ilmenite and are devoid of any hornblende and biotite, whereby clinopyroxene and plagioclase form phenocrysts. Generally, the groundmass is variably altered, whereas clinophenocrysts are comparatively fresh. The clinopyroxene is represented by the composition Wo(37-48)En(43-53)Fs(4-17), with Mg/(Mg + Fe2+) ratios of 0.93-0.73. Compositionally, the clinopyroxenes resemble those from island arc tholeiitic, calc-alkaline and anorogenic tholeiitic rocks. Clinopyroxene-melt geothermobarometry yielded temperatures of 1146 and 1193 degrees C and pressures of 1.4 to 7.0 kbar, suggesting that the clinopyroxene phenocrysts started to grow at variable crustal depths. There is no apparent difference of magma temperatures between different magma affinities. The Fe-Mg partition coefficient between clinopyroxene and melt (K-D (Fe-Mg)(Cpx-Melt) = 0.27) suggests that the parental magmas in equilibrium with clinopyroxene were mostly primitive, with Mg# of 65-79. The REE patterns of parental melts in equilibrium with clinopyroxene phenocrysts resemble those of low-K tholeiitic to middle- to high-K calc-alkaline rocks from the magmatic arcs. The results of this study are mostly consistent with the inferences from the whole-rock geochemistry, and indicate that the major and trace element geochemistry can be effectively used to infer the geochemical affinities of the highly altered basaltic rocks.
Keywords: Yuksekova Complex; clinopyroxene; mineral chemistry; in situ LA ICP-MS analysis; geothermobarometry